Dual S-methoprene and Lysinibacillus sphaericus larvicide use leads to multiple independent, and not cross-resistance in Culex pipiens - Kristina Lopez; Patrick Irwin; Mark Tomek; Robert Holub; Susan Paskewitz; Lyric Bartholomay; Mark Clifton (PLoS ONE, 2025)
S-methoprene, an insect growth regulator, and Lysinibacillus sphaericus (Ls), an entomopathogenic bacterium, are important larvicides used to control Culex pipiens [L.] mosquitoes, the primary vector of West Nile virus, in the Chicago, IL USA region. Resistance to both agents has been documented globally including a report of resistance ratios greater than 100 to S-methoprene in the Chicago region. Laboratory studies have suggested the potential for unidirectional cross-resistance between S-methoprene and Ls, despite differing modes of action. Among wild populations of Cx. pipiens in the Chicago area, this study aimed 1) to assess resistance status to Ls, 2) confirm the presence of S-methoprene resistance ratios >100, 3) determine if higher S-methoprene resistance ratios are associated with higher Ls resistance ratios, or whether Ls resistance arises solely from Ls exposure, and (4) determine the relationship between Ls treatment history and resistance levels of that active ingredient. We assessed susceptibility to both S-methoprene and Ls in 32 Cx. pipiens populations: 19 with S-methoprene exposure but no Ls history, and 13 with multi-year exposure to both larvicide active ingredients. Ls susceptibility was evaluated using dose-response bioassays to estimate LC50, LC90, and resistance ratios. Susceptibility to S-methoprene was tested using diagnostic doses corresponding to resistance ratios of 10 and 100 at the LC50. Resistance ratios to S-methoprene exceeding 10 were detected in 30 of 32 sampled populations. Among the 13 sites with prior Ls exposure, 11 were observed with resistance ratios > 5. In contrast, none of the 19 populations without Ls exposure exhibited Ls resistance, despite exhibiting higher S-methoprene resistance ratios. This lack of overlap supports the conclusion that S-methoprene resistance does not confer cross-resistance to Ls in the studied region. Logistic regression revealed a strong association between Ls treatment history and resistance development. The probability of Ls resistance exceeded 80% after 10 Ls applications within an eight-year period. These findings emphasize the need to develop improved resistance management strategies for larvicidal insecticides.